Pasar Tradisional di Masa Pandemi (Interaksi Sosial Pedagang dan Pembeli di Pasar Sentral Kota Palopo) - Muhammad Ashabul Kahfi; Fitriani Jamaluddin; Astuti Astuti (Jurnal Community, 2021)
Social interaction is one of human needs as homo social. The COVID-19 pandemic has resulted in changes in all aspects of human life, including social interactions. This study aims to determine the changes in social interaction between traders and buyers at the Central Market of Palopo City during the COVID-19 pandemic. This research was conducted by interviewing vegetable traders and buyers in the Central Market of Palopo City. The data are then grouped, to be analyzed using a qualitative model. The results showed that there was a change in the process of social interaction between traders and buyers during the covid-19 pandemic. There is fear and anxiety for most traders and buyers so that it affects the reduced time to shop for buyers. In addition, many traders and buyers have switched to using cellphones to make buying and selling transactions. The results of this study conclude that the COVID-19 pandemic has changed the normal conditions that have been happening in traditional markets. There is a change in the interaction between traders and buyers in traditional markets, which used to interact directly, now they interact virtually.